ANALISIS PERBANDINGAN PERTUMBUHAN PENJUALAN KENDARAAN BERMOTOR TERTENTU SEBELUM DAN SETELAH INSENTIF PPnBM DTP - Lubis, Putri; Solikin, Akhmad (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2024)
The pandemic has stifled the national economy and urged the government to take fiscal action to save the economy. One of them is a tax incentive for four-wheeled vehicles called Pajak Penjualan atas Barang Mewah Ditanggung Pemerintah (PPnBM DTP). The research used a quantitative method in the form of a paired sample t-test to explore the effect of PPnBM DTP on vehicle sales growth and determine the relationship between PPnBM DTP and PPnBM Dalam Negeri. The data used is secondary data in the form of PPnBM values from Laporan Keuangan Pemerintah Pusat and sales of car units sourced from Gaikindo by separating the vehicles to control group and treatment group. It was concluded that PPnBM DTP had an effect on the sales value of all cars that received tax reduction facilities through a significant increase in the treatment group as evidenced by the p value of 0,000. In its implementation, there are several factors that can influence the level of public consumption, including their preferences in purchasing vehicles, brand loyalty, availability of new variants, and the economic conditions of consumers themselves.